Sequelae of Wearing Complete Dentures (Bangladesh Journal of Dental Research & Education, 2013)
The use of complete dentures is not free of trouble. The dentures can produce severe side effects, which if left unchecked will produce, destabilization of occlusion, loss of retention, decreased masticatory efficiency, poor aesthetics, increase ridge resorption, tissue injury. The problems will progress till the stage where the patient will be considered prosthetically maladaptive and cannot wear dentures any more. The interaction of prosthesis and oral environment has several apects. The surface properties of the prosthesis may affect plaque formation. Surface irregularities and microporosities can enhance microbial colonization. Plaque formation is also influenced by: design of prosthesis, health of adjacent mucosa, composition of saliva, salivary secretion rate, oral hygiene, denture wearing habits. Thus, a prosthesis may promote infection of the underlying mucosa, caries and periodontal diseases of the overdenture abutments, perimplantitis (inflammation of the peri-implantal membrane), chemical degradation or corrosion of prosthesis. All these disorders produced/ accelerated in the oral tissues due to the presence of a denture are grouped as sequelae of wearing complete dentures. Sequelae of complete denture wear can be divided into direct and indirect types depending on the effect of the prosthesis on the tissues are discussed and hence the current literature is reviewed. DOI: http://dx.doi.org/10.3329/bjdre.v3i2.16614 Bangladesh Journal of Dental Research & Education Vol.3(2) 2013: 51-56